Risk Management Planning in E-Commerce Companies PT. SIMPEL OM UNGGULAN "SIMPEL OMâ€ - Mega Ekania; Edi Hamdi; Rhian Indradewa; Ferryal Abadi (Syntax Idea, 1939)
Risk Management in Simple OM is the process of identifying, measuring, and analyzing risks that can affect the performance, security, and trustworthiness of an eCommerce business. This risk can come from internal or external factors, such as networks, buyers, sellers, payments, shipping, law and others. Risk management aims to reduce the negative impact of risks and increase the chances of eCommerce business success